2002
DOI: 10.1002/gps.671
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic therapy with lithium in elderly patients with unipolar major depression

Abstract: This preliminary study suggests that long-term low dose lithium therapy is well tolerated and protects elderly patients from a relapse of depressive illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 17 publications
0
26
0
5
Order By: Relevance
“…Twenty-one RCTs were excluded because they did not use antidepressants but acetyl-L-carnitine (Bella et al, 1990;Gecele et al, 1991), ACTH 4-9 analog (Frederiksen et al, 1985), adinazolam (Feighner et al, 1990), brofaromine (Moller and Volz, 1993), diclofensine (Gentili et al, 1984;Jansen et al, 1982), flupenthixol (Hostmaelingen et al, 1989), lithium (Wilkinson et al, 2002), methylphenidate (Wallace et al, 1995), nimodipine (Taragano et al, 2001(Taragano et al, , 2005, perphenazine (Meyers et al, 2001), procaine (Aslan et al, 1986;Bălăceanu-Stolnici et al, 1996), rolipram (Behnke et al, 1992), St. John's Wort (Harrer et al, 1999), sulpiride (Kivelä and Lehtomäki, 1987), tryptophan (Cooper and Datta, 1980;Rousseau, 1987), or combined fluphenazine/nortriptyline (Brodie et al, 1975).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one RCTs were excluded because they did not use antidepressants but acetyl-L-carnitine (Bella et al, 1990;Gecele et al, 1991), ACTH 4-9 analog (Frederiksen et al, 1985), adinazolam (Feighner et al, 1990), brofaromine (Moller and Volz, 1993), diclofensine (Gentili et al, 1984;Jansen et al, 1982), flupenthixol (Hostmaelingen et al, 1989), lithium (Wilkinson et al, 2002), methylphenidate (Wallace et al, 1995), nimodipine (Taragano et al, 2001(Taragano et al, , 2005, perphenazine (Meyers et al, 2001), procaine (Aslan et al, 1986;Bălăceanu-Stolnici et al, 1996), rolipram (Behnke et al, 1992), St. John's Wort (Harrer et al, 1999), sulpiride (Kivelä and Lehtomäki, 1987), tryptophan (Cooper and Datta, 1980;Rousseau, 1987), or combined fluphenazine/nortriptyline (Brodie et al, 1975).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the administration of lithium for recurrent unipolar depression remains controversial [Price and Henninger, 1994] despite several positive reports in naturalistic [Lepkifker et al, 1985] and double-blind [Peselow et al, 1982] studies. Recently, in a placebo-controlled study, Wilkinson et al [2002] reported that the addition of lithium to an antidepressant among older adult patients was associated with increased likelihood to sustain remission over a 2-year period. Our findings add to the limited literature on the subject of lithium prophylaxis in older adults and confirm previous suggestions that the positive effect of lithium noted in the young may also be noted in the middle-aged and older adults.…”
Section: Discussionmentioning
confidence: 98%
“…Numerically fewer deaths occurred in the lithium group in all trials, except three. In two of these trials (30,45), the number of deaths was the same in both groups; in the other small trial (31), one death occurred in the lithium-treated group, and none occurred in the placebo group.…”
Section: Mortality From All Causesmentioning
confidence: 92%
“…In the majority of trials there were no deaths (Figure 4). Six of the 12 trials were informative for lithium versus placebo (18,24,31,39,40,45), three for lithium versus tricyclic antidepressants (27,28,39), two for lithium versus carbamazepine (29,30), and one for lithium versus lamotrigine (17). There were fewer deaths overall among the patients who received lithium (nine versus 22, Peto odds ratio=0.42, 95% CI=0.21-0.87, p=0.02) (χ 2 = 4.98, df=11, p=0.93, chi-square test for heterogeneity).…”
Section: Mortality From All Causesmentioning
confidence: 99%